Life Insurance Products for Pensions in Vietnam - Tuệ, Nguyễn Đăng (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 31 No 5E, 2015)
Abstract: In addition to the Government’s social insurance, pension products by life insurance companies provide more options for individuals for retirement preparation. This article aims to give a brief overview of life insurance products for pensions inVietnam. It describes the pension system inVietnam and shows the needs for private pension products. The article summarizes the basic information about the development of life insurance and pension products inVietnam. The article also highlights various features of life insurance products for pensions such as initial conditions for participation, guaranteed interest rate, main benefits and costs. The author then makes some recommendations forVietnam in developing pension products to cope with the market demand. Keywords: Pension products, insurance company, Vietnam